Prevalence of voiding and defecatory dysfunction in postmenopausal women with pelvic organ prolapse: a prospective observational study - Saravanan, Nanthini; Ebenezer, Emily Divya; Londhe, Vaibhav; Varghese, Lilly; Kekre, Aruna N.; Jeyaseelan, Vishalakshi; Kekre, Nitin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Primary objective of this work was to study the prevalence of voiding and defecatory dysfunction in women with pelvic organ prolapse and correlate the stage and compartment of prolapse with voiding and defecatory dysfunction. The secondary objective was to correlate stage of prolapse with flow rate and post void residue and to study the voiding dysfunction in pelvic organ prolapse. Methods: A prospective observational cohort study in 120 post-menopausal women scheduled for vaginal hysterectomy pelvic floor repair. Short form of pelvic floor distress inventory (PFDI-20) and International prostate symptom questionnaire I-PSS score for Lower urinary tract symptoms (LUTS)was employed. Results: The prevalence of voiding dysfunction in this study was 78% and defecatory dysfunction was 77%. Higher stage of prolapse had significant correlation with voiding dysfunction. (P value was 0.028). Women with posterior compartment defect had more voiding dysfunction with the significant P value (p value was 0.04). Pre-operative voiding dysfunction resolved post operatively in 86%, the p<0.000 which was highly significant. Conclusions: Women with pelvic organ prolapse had high prevalence of voiding and defecatory dysfunction. Stages of prolapse have positive correlation with voiding dysfunction. Pre-operative voiding dysfunction resolved after vaginal hysterectomy and pelvic floor repair.